Current status of usage of ivermectin in the management of COVID - Swetha Ilangovan; Dhanraj Ganapathy; Nabeel Ahmed; Kiran Kumar Pandurangan; Subhabrata Maiti (Wolters Kluwer Medknow Publications, 2022)
The antibacterial, antiviral, and anticancer properties of ivermectin make it a wonder drug with a wide range of possible applications. It works against a variety of microorganisms, including viruses. Ivermectin has a wide range of antiviral effects, according to in vivo research in animal models. Because ivermectin is involved in a range of biological processes, it could be a promising therapeutic candidate for viruses such as COVID-19 and other positive-sense single-stranded RNA viruses. The study aims to analyze the awareness about the current status of usage of ivermectin in management of COVID among students studying in a private dental college. A study based on questionnaire was organized among students studying in a private dental college in Tamil Nadu. The subjects were asked a series of structural questions based on the usage of ivermectin in management of COVID. The questionnaire was prepared with 10 questions. 150 individuals completed the questionnaire; all of their answers were tallied in excel and imported into SPSS. For statistical analysis, the Chi-square test was performed. Excel was used to tabulate and enter the data, and the SPSS package software was used to analyze it. The study's threshold for statistical significance was set at P < 0.05. From this study, we found that the students had limited knowledge about the usage of ivermectin for management of COVID. More studies should be conducted to widen the knowledge among the students about the current affairs of the world.